POSMODERNISME DALAM ISU INTERNASIONAL: STUDI KASUS FILM BLACK WIDOW DAN FILM SRI ASIH - Soeryantoputri, Letisia Karina (Universitas Jenderal Ahmad Yani, 2024)
Through Postmodernism, issues in the global world have been through modernization and able to be seen from another perspective. Variety of films with theme of superheroes, such as Black Widow and Sri Asih, have attracted attention significantly. Both films can be a medium to translate messages and realities in current society. Therefore, this research focuses on the meaning of international issues through Black Widow and Sri Asih based on Postmodernism theory. The result shows that the meaning of social issues from both films are valid and well-suited with current reality. Furthermore, it describes hidden meanings which are also related to social issues, especially prominent issues that being concerned by international organizations. The conclusion of this research is the international world no longer depends on traditional media to see current international issues. Modern media such as films are possible to used as well to interpret the intended message.